Overwintering insect (Arthropoda: Insecta) biodiversity in pistachio orchards of the Middle Euphrates Valley, Turkey - Sabuncu, Yeliz; Mamay, Mehmet; Özgen, İnanç (My University, 2021)
This study was conducted to determine the overwintering insect biodiversity in pistachio orchards of the Middle Euphrates Valley, Turkey during 2017 and 2018 by artificial overwintering shelters. Artificial overwintering shelters were established in five pistachio orchards in Şehirbağı, Karabaş, Meyanca, Baraj and Ekenek locations. Ten trees were selected within each orchard and five of these were covered with a burlap sack and the rest were covered with corrugated cardboard through September and January. Twenty insect species belonging to15 families and 4 orders were recorded from the studied orchards. These recorded species were; Oenopia conglobata (Linnaeus, 1758) (Coleoptera: Coccinellidae), Hippodamia variegata (Goeze, 1777) (Coleoptera: Coccinellidae), Coccinella septempunctata (Linnaeus,1758) (Coleoptera: Coccinellidae), Scymnus rubromaculatus (Goeze, 1777), Loraphodius suarius (Falderman, 1835) (Coleoptera: Aphodiidae), Drasterius bimaculatus (Rossi, 1790) (Coleoptera: Elateridae), Hermaeophaga (=Orthocrepis) ruficollis (Lucas, 1849) (Coleoptera: Chrysomelidae), Bangasternus orientalis (Capiomont, 1873) (Coleoptera: Curculionidae), Aulacobaris coerulescens (Scopoli, 1763) (Coleoptera: Curculionidae), Capnodis carbonaria (Klug, 1829) (Coleoptera: Buprestidae), Tentyria euphratica (Girard 1966) (Coleoptera: Tenebrionidae), Malachius rubidus (Erichson, 1840) (Coleoptera: Malachiidae), Piezodorus lituratus (Fabricius, 1794) (Hemiptera: Pentatomidae), Liorhyssus hyalinus (Fabricius, 1794) (Hemiptera: Rhopalidae), Dolycoris baccarum (Linnaeus, 1758) (Heteroptera,: Pentatomidae), Eurygaster integriceps (Puton, 1881) (Hemiptera: Scutelleridae), Centrocoris volxemi (Puton, 1878), (Hemiptera: Coreidae), Geocoris luridus (Fieber, 1844) (Heteroptera: Lygaeidae), Chrysoperla carnea (Stephens, 1836) (Neuroptera: Chrysopidae) and Schistocerca gregaria (Forskol, 1775) (Orthoptera: Acrididae). The results revealed that burlap sack and corrugated cardboard artificial winter shelters can be used to monitor harmful and beneficial insect fauna overwintering in fruit orchards. The results provide empirical information on the existence of overwintering insect species in pistachio orchards. Thus, integrated pest management strategies should be developed for the pistachio orchards in the study area based on these results.
Keywords: Biodiversity; Euphrates; Pistachio; Insect fauna; Overwintering